Políticas do desejo: considerações sobre psicanálise e feminismo em A câmara sangrenta e outras histórias, de Angela Carter - Isadora Saraiva Vianna de Resende Urbano (2022)
The present work starts from the perspective that the stories of The Bloody Chamber are, at the same time, literature and criticism, providing in fictional language the keys to Carter's interpretations of the latent content of the fairy tales from which her tales originate. With this starting point, we seek to investigate the critical position of the stories in the collection, individually and, in some points, comparatively, trying to analyse the relationship between Carter’s stories and the works they address, especially the tales by Perrault and Grimm, since most of the stories in The Bloody Chamber are related to its narratives, although they also contain the most diverse intertextual references. To carry out the analysis, we tried to articulate the close reading of the stories with the most significant intertexts that we identified, in addition to resorting to paratexts such as manuscripts, drafts, interviews and journalistic texts by Carter and the critical material already produced about the author’s work, and selecting the most convenient theoretical contribution to each case, since each story required a specific path of analysis and research. Through the investigation, we observed that Carter appropriates the latent material of fairy tales, putting it under the spotlight, that is, placing it in the narrative foreground, in order to create stories that subvert, extrapolate, update and pose questions about the contents that fairy tales would bring in latency, hence the importance of the dialogue with The Uses of Enchantment (1976), by Bruno Bettelheim. We also note that, relying mainly on a procedure governed by difference and deconstruction – that is, alternating variables such as narrative voice, agency, degree of realism and psychic complexity, for instance – Carter’s stories emphasise her feminist critical position face to women’s oppression, and that lead us through different paths to questions about challenges such as the construction of one’s own identity, love encounters and disagreements, the approximation between the erotic and violence, the importance of social and material conditions in the subordination of women and the contradictions that cross the interests and desires of these characters; to these questions, the stories of The Bloody Chamber offer glimpses of alternative horizons, opening up a range of possibilities beyond those offered by classic fairy tales.